(untitled) (Bangladesh Veterinarian, 2018)
The prevalence and risk factors associated with subclinical mastitis in crossbred Friesian cows in selected dairy farms were studied using California Mastitis Test (CMT). A total of 287 cows and 1148 quarters were examined. Cow parity, age, body condition score (BCS), milk yield and lactation stage were collected by using pretested questionnaire. The prevalence of subclinical mastitis was 41.1%. Among tested cows, 15.8% showed moderate and 5.5% strong reaction to CMT (P<0.05). Among quarters, 24.6% quarters were affected with subclinical mastitis of which 10.1% showed moderate and 1.9% strong reaction to CMT (P<0.05). Cows at parity 2 to 4 had a significantly (P<0.05) higher prevalence (46.5%) than those at parity 5 to 10 (30.3%). The prevalence of subclinical mastitis in different age groups of cows did not vary significantly. The cows with BCS 3.5 to 4 had significantly (p<0.05) higher prevalence of subclinical mastitis (43.5%) than those with BCS 4.5 (25.9%). Cows with 11-27 litres of milk yield had significantly (P<0.05) higher subclinical mastitis (44.3%) than that of 1 to 5 litres of their counterpart (38.6%). Cows at 31 to 90 (44.3%) days lactation had significantly (P<0.05) higher prevalence of subclinical mastitis than those at 181 to 285 days (37.2%). It is suggested that the prevalence of subclinical mastitis was influenced by the parity, BCS, milk yield and lactation stage in crossbred Friesian cows in Bangladesh. Bangl. vet. 2017. Vol. 34, No. 2, 42-51